High-performance silicon-based composite negative pole piece as well as preparation method and application thereof
By using defective carbon nanotubes in lithium-ion secondary batteries to improve the performance of silicon-based anode materials, the problems of electrode cracking and powderization caused by high volume expansion rate of silicon-based anode materials are solved, and high energy density and long cycle life are achieved The preparation of silicon-based composite negative electrode sheets simplifies the preparation process and reduces costs.
Patent Information
- Application Number
- CN202411372697.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The silicon-based negative electrode material in lithium-ion secondary batteries has caused electrode cracking, powdering and falling off due to the high volume expansion rate, which consumes electrolyte, affects the cycle life. The existing composite material preparation methods are complex and costly, making it difficult to achieve commercial application.
By adding defective carbon nanotubes to the silicon-based active material, the three-dimensional structure of the silicon-based negative electrode is reconstructed by using the mechanical-chemical interface coupling, and the silicon-based clusters are anchored in situ to enhance its cyclic performance.
It significantly improves the cycle stability and rate performance of silicon-based anode materials, simplifies the preparation process, reduces costs, is easy to produce on a large scale, and extends the energy density and cycle life of the battery.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion battery electrode materials, and in particular relates to silicon-based negative electrode materials, preparation methods thereof, and lithium-ion batteries or lithium-ion secondary batteries containing the same, and specifically relates to a high-performance silicon-based composite negative electrode sheet, a preparation method thereof, and applications thereof. Background Art
[0002] Lithium-ion secondary batteries have been widely used in various electronic products, electric vehicles and large energy storage devices due to their high energy density and good cycle performance. With the development of the market, higher requirements have been put forward for their performance. The rapidly iterating lithium-ion secondary batteries have made certain progress in their energy density and cycle life. In particular, with the introduction of silicon-based negative electrode materials, the capacity of lithium-ion secondary battery negative electrodes has made great progress, thanks to the higher theoretical capacity of silicon-based negative electrode materials. Among them, single silicon shows a theoretical capacity of about 4200mAh / g, and sub-silicon SiO x It has a theoretical capacity of about 2400mAh / g.
[0003] Silicon-based negative electrode materials are the first choice for improving the performance of lithium-ion secondary batteries, but their large-scale application is severely restricted by problems such as high volume expansion rate. This will cause the electrode to crack or even pulverize and fall off, and the fresh silicon surface produced by the fragmentation will consume the electrolyte to form a new SEI film. As the cycle progresses, the silicon-based negative electrode will continue to pulverize and form SEI, consuming the electrolyte, resulting in the generation of irreversible capacity and rapid decay of the electrode capacity.
[0004] During the cyclic lithiation process, the continuous expansion and cracking process will cause some silicon-based particles to lose electrical contact and exhibit electrochemical inertness. Some silicon-based particles will become "dead silicon", and some lithium ions embedded in them will also be inactivated and cannot be released, resulting in irreversible capacity, which seriously affects the cycle life of the silicon-based negative electrode.
[0005] At present, silicon-based materials can only be added to graphite negative electrodes at a low content to form composite materials for use. Conventional silicon-based negative electrode structure design methods include core-shell, yolk-shell structure, and nanocarbon material network. Although they can improve mass transfer and stabilize the structure, they also face the problems of complex preparation and high cost, making it difficult to truly commercialize them. In order to further promote the industrial application of silicon-based negative electrode materials and improve the energy density of commercial lithium-ion secondary batteries, the development of silicon-based negative electrode materials with high energy density and long cycle life has become the current focus and difficulty, which has great research significance and good application prospects. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention proposes a high-performance silicon-based composite negative electrode plate and a preparation method thereof, which improves the performance of the negative electrode plate containing silicon-based active materials in lithium-ion secondary batteries by adding defective carbon nanotubes, and utilizes the strong local stress generated by the silicon-based active materials during the charging and expansion stage to induce high strain on the defective carbon nanotubes, thereby enhancing the chemical activity of the atoms at the defective sites, thereby generating a "stress-chemical interface coupling reaction" between lithium atoms and silicon group clusters under the action of lithium atoms, and in-situ anchoring the silicon group clusters to stabilize their cycle performance.
[0007] Furthermore, the present invention also provides the use of the high-performance silicon-based composite negative electrode plate in the preparation of lithium-ion batteries or lithium-ion secondary batteries.
[0008] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0009] A method for preparing a high-performance silicon-based composite negative electrode, using single-walled carbon nanotubes containing defects, doping elements or functional groups to improve the silicon-based negative electrode, reconstructing the three-dimensional structure of the silicon-based negative electrode through mechanical-chemical interface coupling, and in-situ anchoring silicon group clusters to improve the performance of the prepared silicon-based negative electrode;
[0010] The preparation method specifically comprises the following steps:
[0011] Step 1: dispersing a certain amount of surfactant and a certain amount of defective single-walled carbon nanotubes in a solvent I by ultrasonic treatment, and then centrifuging to remove agglomerated particles to obtain a stable and uniform dispersion A;
[0012] Step 2: Mix the silicon-based active material, the binder, the carbon-based conductive agent and the dispersion A in step 1 in a certain proportion by wet mixing to prepare a mixed slurry;
[0013] Step 3: coating the mixed slurry prepared in step 2 on a conductive substrate, drying, and cutting to obtain the high-performance silicon-based composite negative electrode plate.
[0014] Furthermore, the surfactant described in step 1 is one or more of carboxymethyl cellulose, polyvinyl pyrrolidone, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, and sodium lignin sulfonate, preferably carboxymethyl cellulose.
[0015] Furthermore, the molecular structure of the defective single-walled carbon nanotube described in step 1 contains one or more of four-membered ring defects, five-membered ring defects, seven-membered ring defects, and eight-membered ring defects, or is doped with one or more of elements such as oxygen, fluorine, nitrogen, sulfur, selenium, boron, phosphorus, and lithium.
[0016] Furthermore, the solvent I described in step 1 is one or more of water, ethanol, N-methylpyrrolidone, etc.
[0017] Furthermore, the mass ratio of the defective single-walled carbon nanotubes to the surfactant in step 1 is (0.01-20):1.
[0018] Furthermore, the mass ratio of the defective single-walled carbon nanotubes in step 1 to the solvent I is (0.001-1):1.
[0019] Furthermore, the ultrasonic treatment method in step 1 is to use an ultrasonic crusher or an ultrasonic cleaning machine to treat at a temperature of -10 to 10°C for 1 to 3 hours; the ultrasonic power is 100 to 2000 watts; further preferably, when performing the ultrasonic treatment, the ultrasonic treatment is continued for 1 to 3 hours with a program of ultrasonic 2 to 3 seconds and then 2 to 3 seconds on.
[0020] Furthermore, the centrifugal speed in step 1 is 500 to 4000 rpm, and the centrifugal time is 5 to 100 minutes.
[0021] Furthermore, in step 2, the mass ratio of the silicon-based active material, the binder, the carbon-based conductive agent and the defective single-walled carbon nanotube is (0.1-96):(0.01-25):(0.01-25):(0.001-5).
[0022] Furthermore, the silicon-based active material in step 2 is one or more of elemental silicon, silicon monoxide and silicon-carbon composite materials, or a composite of one or more of elemental silicon, silicon monoxide and silicon-carbon composite materials and graphite.
[0023] Furthermore, the silicon-based active material is preferably silicon dioxide SiO x , wherein the atomic ratio of silicon to oxygen in silicon oxide is 4:1 to 0.25:1; or, the silicon oxide SiO x The atomic percentage of silicon is 61% to 64%, preferably 62.5%.
[0024] Alternatively, as another preferred technical solution, the silicon-based active material is preferably carbon-coated silicon, and the carbon-coated silicon is silicon oxide SiO x and a carbon coating layer, wherein the carbon coating layer is obtained by carbonizing pitch, silicon dioxide SiO x The mass ratio of the carbon coating layer is (3-9):1, preferably 8:2 or 9:1.
[0025] Furthermore, the carbon-coated silicon is made of silicon oxide SiO x After mixing with asphalt, it is carbonized at high temperature and annealed. The specific preparation method is: using a mixer to mix silicon dioxide SiO xIt is mixed with asphalt at a certain mass ratio at a speed of 400-600 rpm for 10-12 hours, then softened at 300-330°C for 1-2 hours in an argon atmosphere, then heated to 800-1000°C and carbonized for 2-3 hours, and cooled naturally to obtain.
[0026] Alternatively, as another preferred technical solution, the silicon-based active material is preferably a mixture of carbon-coated silicon and graphite, wherein the mass ratio of carbon-coated silicon to graphite is 1:(3-9), preferably 2:8, 1:9.
[0027] Furthermore, the binder in step 2 is one or more of carboxymethyl cellulose, sodium alginate, ammonium alginate, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylic acid (PPA), lithiated polyacrylic acid (lithiated PPA), styrene-butadiene rubber and polystyrene butadiene copolymer.
[0028] Further preferably, the binder is a mixture of carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR), with a mass ratio of 1:(1-2), preferably 1:1.
[0029] Furthermore, the carbon-based conductive agent in step 2 is one or more of artificial graphite, natural graphite, hard carbon, soft carbon, acetylene black, Ketjen black, carbon black Super P, graphene, multi-walled carbon nanotubes and fibrous carbon.
[0030] Furthermore, in step 2, during wet mixing, a magnetic stirrer, a ball mill mixer, an oscillating mixer, a rotary mixer, a V-type mixer or the like is used for stirring and mixing, and the stirring time is 12 h to 36 h, and the rotation speed is 50 to 2000 rpm.
[0031] Further preferably, in step 2, during wet mixing, solvent II may be added, and the added solvent II may be one or more of water, ethanol, N-methylpyrrolidone, and the like.
[0032] Furthermore, the conductive substrate in step 3 is any one of copper foil, carbon-coated copper foil, copper mesh, foam copper, stainless steel, stainless steel mesh, carbon paper and carbon cloth.
[0033] Furthermore, in step 3, when the mixed slurry is coated, the loading amount of the mixed slurry is less than or equal to 1.2 mg / cm 2 .
[0034] Furthermore, the drying method described in step 3 is to use a blast drying oven, a vacuum drying oven, or a box furnace for drying, the drying temperature is 50-120°C, and the drying time is 12h-36h; preferably, the vacuum degree when vacuum drying is performed in a vacuum drying oven is ≤133Pa.
[0035] Furthermore, the present invention also provides a high-performance silicon-based composite negative electrode plate prepared by the above method, which has good first efficiency, rate performance and cycle stability and can be used to prepare lithium-ion batteries.
[0036] Furthermore, based on a general inventive concept, the present invention also provides the use of the high-performance silicon-based composite negative electrode plate in the preparation of lithium-ion batteries or lithium-ion secondary batteries.
[0037] Further, based on a general inventive concept, the present invention also provides a method for preparing a lithium ion battery or a lithium ion secondary battery using the high-performance silicon-based composite negative electrode sheet, comprising the following steps:
[0038] a) Preparation of electrode sheet: using a puncher or a slicer to make the high-performance silicon-based composite negative electrode sheet into a button-type electrode disc;
[0039] b) Button cell assembly: Using the metal lithium sheet as the counter electrode, the electrode disc prepared in step a), the metal lithium sheet (as the counter electrode), the separator, and the electrolyte are assembled into a button cell. The battery model is a CR2032 button cell.
[0040] Specifically, in step a), the diameter of the electrode disc is 12 mm.
[0041] Specifically, in the battery assembled in step b), the separator type is Celgard 2400, and the electrolyte is 1M LiPF added with 5% fluoroethylene carbonate FEC. 6 / EC+DMC(V / V=1:1).
[0042] Furthermore, based on a general inventive concept, the present invention also provides a lithium ion battery or a lithium ion secondary battery prepared by the above method.
[0043] Compared with the prior art, the advantages of the present invention are:
[0044] 1. The present invention provides a method for preparing a high-performance silicon-based composite negative electrode sheet that is simple to operate, has significant effects and is easy to mass produce, and has the advantages of high commercial value and easy mass production.
[0045] 2. The present invention can utilize the addition of defective carbon nanotubes to improve the performance of negative electrode sheets containing silicon-based active materials in lithium-ion secondary batteries. The strong local stress generated by the silicon-based active materials during the charging expansion stage is utilized to induce high strain on the defective carbon nanotubes, thereby enhancing the chemical activity of atoms at the defective sites. As a result, under the action of lithium atoms, a "stress-chemical interface coupling reaction" is generated between the silicon group clusters, thereby anchoring the silicon group clusters in situ and avoiding electrical contact loss. At the same time, the silicon group clusters can also separate the defective carbon nanotube bundles and enhance the transmission rate of lithium ions.
[0046] The present invention utilizes "stress-chemical interface coupling" to reconstruct the three-dimensional structure within the silicon-based negative electrode, thereby stabilizing the electrode structure and promoting mass transfer, thereby effectively improving its rate and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is a SEM morphology image of the high-performance silicon-based composite negative electrode prepared in Example 1;
[0048] Figure 2 This is a TEM morphology of defective carbon nanotubes after cycling of the high-performance silicon-based composite negative electrode prepared in Example 1;
[0049] Figure 3 The cycle performance diagrams of Examples 1 and 2 of the present invention and Comparative Examples 1 and 2;
[0050] Figure 4 This is a cycle performance diagram of Example 3 of the present invention;
[0051] Figure 5 4 and 5 are cycle performance diagrams of embodiments 4 and 5 of the present invention;
[0052] Figure 6 Graphs showing the cycle performance of embodiments 2, 6 and 7 of the present invention;
[0053] Figure 7 This is a cycle performance diagram of Example 8 of the present invention. DETAILED DESCRIPTION
[0054] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0055] Unless otherwise specified, the experimental methods used in the following examples and comparative examples are all conventional methods; the reagents, raw materials, etc. used in the following examples, unless otherwise specified, are all conventional commercially available products and can be obtained from commercial channels.
[0056] The silicon dioxide SiO used in the following examples and comparative examples is x It is in powder form and is produced by Shanghai Xiangtian Nanomaterials Co., Ltd. with the product number XT-SIO-5U. Its median particle size D50 is 5μm and the atomic proportion of silicon is 62.5%.
[0057] Example 1
[0058] Example 1 provides a method for preparing a high-performance silicon-based composite negative electrode plate, the specific steps of which are:
[0059] Step 1: 10 g of surfactant (carboxymethyl cellulose) and 5 g of single-walled carbon nanotubes with five-membered ring and seven-membered ring defects (preparation method reference Wang, Haolin, et al. "What Is the Real Origin of Single-Walled Carbon Nanotubes for the Performance Enhancement of Si-Based Anodes?" Journal of the American Chemical Society 2024, 146 (25), 17041-17053) were added to 85 g of ultrapure water, and then placed in an ultrasonic crusher under 1500 watts of ultrasonic power and 0°C water bath conditions, and ultrasonic treatment was continued for 2 hours with a program of ultrasonic 3s and 3s on and off, and then centrifuged at 2000 rpm for 30 minutes, and the supernatant was taken as a dispersion A of defective single-walled carbon nanotubes with stable and uniform dispersion;
[0060] Step 2: Take silicon oxide SiO x , a binder (CMC+SBR), carbon black Super P (carbon-based conductive agent, purchased from Shenzhen Kejing Zhida Technology Co., Ltd., brand CAS1333-86-4) and the defective single-walled carbon nanotube dispersion A in step 1 are wet mixed, and the resulting mixture is stirred on a stirring table of a magnetic stirrer at a speed of 400 rpm for 24 hours to prepare a slurry;
[0061] Among them, silicon dioxide SiO x The mass ratio of the binder, the carbon-based conductive agent and the single-walled carbon nanotubes with five-membered ring and seven-membered ring defects is 90:5:4:1; the mass ratio of CMC and SBR in the binder is 1:1;
[0062] Step 3: Use a coating machine to evenly coat the slurry from step 2 onto the surface of the copper foil. The loading amount of the slurry is about 1.2 mg / cm 2 After drying at 60° C. for 24 hours in a vacuum drying oven (vacuum degree ≤ 133 Pa), the high-performance silicon-based composite negative electrode sheet is obtained by cutting.
[0063] The surface morphology of the high-performance silicon-based composite negative electrode prepared in Example 1 was characterized by scanning electron microscopy. The obtained SEM image is as follows: Figure 1 The morphology of defective carbon nanotubes after the negative electrode sheet in Example 1 was characterized by a transmission electron microscope, and the obtained TEM image is as shown in FIG. Figure 2 As shown, from Figure 1 and Figure 2In the figure, it can be clearly seen that the powdered silicon-based particles are anchored on the surface of defective single-walled carbon nanotubes.
[0064] Example 2
[0065] Example 2 provides a method for preparing a high-performance silicon-based composite negative electrode plate. The preparation method of Example 2 is different from that of Example 1 in that:
[0066] In step 2, silicon dioxide SiO x The mass ratio of the binder, the carbon-based conductive agent and the single-walled carbon nanotubes with five-membered ring and seven-membered ring defects is 90:5:3:2, and the other steps and conditions are the same as those in Example 1.
[0067] Example 3
[0068] Example 3 provides a method for preparing a high-performance silicon-based composite negative electrode plate. The preparation method of Example 3 is different from that of Example 1 in that:
[0069] In step 2, the silicon dioxide SiO x The carbon-coated silicon is replaced by carbon-coated silicon, and the other steps and conditions are the same as those in Example 1. x and the carbon coating formed by carbonization of asphalt, the carbon-coated SiO x The mass ratio to the carbon coating is 8:2;
[0070] The carbon-coated silicon is made of silicon oxide SiO x After mixing with asphalt, it is carbonized at high temperature and annealed. The specific preparation method is: using a mixer to mix silicon dioxide SiO x It is mixed with asphalt at a mass ratio of 8:2 at a speed of 500 rpm for 12 hours, then softened at 310°C for 2 hours in an argon atmosphere, then heated to 900°C for carbonization for 2 hours, and naturally cooled to obtain.
[0071] Example 4
[0072] Example 4 provides a method for preparing a high-performance silicon-based composite negative electrode plate. The preparation method of Example 4 is different from that of Example 1 in that:
[0073] In step 2, the silicon dioxide SiO x The mixture of carbon-coated silicon and artificial graphite (purchased from Keda New Materials Co., Ltd., product model KD-1) was replaced, and the other steps and conditions were the same as those in Example 1;
[0074] Among them, the mass ratio of carbon-coated silicon to artificial graphite is 2:8; carbon-coated silicon is composed of silicon oxide SiO x and the carbon coating formed by carbonization of asphalt, the carbon-coated SiOx The mass ratio of the carbon-coated silicon to the carbon-coated layer is 8:2. The specific preparation method of the carbon-coated silicon is the same as that in Example 3.
[0075] Example 5
[0076] Example 5 provides a method for preparing a high-performance silicon-based composite negative electrode plate. The preparation method of Example 5 is different from that of Example 1 in that:
[0077] In step 2, the silicon dioxide SiO x The mixture of carbon-coated silicon and artificial graphite (purchased from Keda New Materials Co., Ltd., product model KD-1) was replaced, and the other steps and conditions were the same as those in Example 1;
[0078] Among them, the mass ratio of carbon-coated silicon to artificial graphite is 1:9; carbon-coated silicon is composed of silicon oxide SiO x and the carbon coating formed by carbonization of asphalt, the carbon-coated SiO x The mass ratio of the carbon-coated silicon to the carbon-coated layer is 8:2. The specific preparation method of the carbon-coated silicon is the same as that in Example 3.
[0079] Example 6
[0080] Example 6 provides a method for preparing a high-performance silicon-based composite negative electrode plate. The preparation method of Example 6 is different from that of Example 2 in that:
[0081] In step 2, the binder used was replaced with polyacrylic acid (PAA, purchased from Dongguan Kelude New Energy Technology Co., Ltd., item number MA-EN-BI-0015), and the other steps and conditions were the same as those in Example 2.
[0082] Example 7
[0083] Example 7 provides a method for preparing a high-performance silicon-based composite negative electrode plate. The preparation method of Example 7 is different from that of Example 2 in that:
[0084] In step 2, the binder used is replaced by lithiated polyacrylic acid (lithiated PAA) (PAA-Li, purchased from Dongguan Kelude New Energy Technology Co., Ltd., product number MA-EN-BI-0013), and the other steps and conditions are the same as in Example 2.
[0085] Example 8
[0086] Example 8 provides a method for preparing a high-performance silicon-based composite negative electrode plate. The preparation method of Example 8 is different from that of Example 2 in that:
[0087] In step 2, the binder used was replaced with sodium alginate (purchased from Dongguan Kelude New Energy Technology Co., Ltd., item number MA-EN-BI-0006), and the other steps and conditions were the same as in Example 2.
[0088] Comparative Example 1
[0089] The defective single-walled carbon nanotubes used in step 1 of Example 1 were replaced with multi-walled carbon nanotubes (purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., item number XFM19, length 20-30 μm), and the other steps and conditions were the same as in Example 1.
[0090] Comparative Example 2
[0091] Step 1: Take silicon oxide SiO x , binder (CMC+SBR) and carbon black Super P (carbon-based conductive agent, purchased from Shenzhen Kejing Zhida Technology Co., Ltd., brand CAS1333-86-4), were wet mixed, and the resulting mixture was stirred on a magnetic stirring table at a speed of 400 rpm for 24 hours to prepare a slurry;
[0092] Among them, silicon dioxide SiO x The mass ratio of the binder (CMC+SBR) and carbon black Super P is 90:5:5; the mass ratio of CMC and SBR in the binder is 1:1;
[0093] Step 2: Use a coating machine to evenly coat the slurry from step 2 onto the surface of the copper foil. The loading amount of the slurry is about 1.2 mg / cm 2 After drying at 60° C. for 24 hours in a vacuum oven (vacuum degree ≤ 133 Pa), the silicon-based negative electrode sheet of Comparative Example 2 was obtained.
[0094] Performance Testing
[0095] The products prepared in Examples 1-8 and Comparative Examples 1-2 were assembled into batteries and subjected to electrochemical performance tests (the test method refers to Wang, Haolin, et al. "What Is the Real Origin of Single-Walled Carbon Nanotubes for the Performance Enhancement of Si-Based Anodes?" Journal of the American Chemical Society 2024, 146 (25), 17041-17053). The specific method steps are as follows:
[0096] a) Preparation of electrode sheets: The negative electrode sheets prepared in Examples 1 to 8 and Comparative Examples 1 to 2 were made into button-type electrode discs with a diameter of 12 mm using a puncher or a slicer;
[0097] b) Button cell assembly and performance test: Using a CR2032 button cell model, with a metal lithium sheet as the counter electrode, a Celgard 2400 diaphragm, and a 1M LiPF electrolyte 6 / EC+DMC (V / V=1:1), with 5% fluoroethylene carbonate FEC added, the electrolyte was purchased from Suzhou Duoduo Chemical Technology Co., Ltd., with the item number LB-007, and the electrode disc prepared in step a), the metal lithium sheet (as the counter electrode), the diaphragm, and the electrolyte were assembled into a button cell.
[0098] The cycle performance test was carried out under the following conditions: after 3 activation cycles at 0.05A / g or 0.1A / g, constant current charge and discharge cycles were carried out at a current density of 0.5A / g or 1A / g, and the charge and discharge voltages were limited to 0.01~2V.
[0099] According to the above battery assembly and testing method, the cycle performance of the high-performance silicon-based composite negative electrode sheets prepared in Examples 1 to 8 of the present invention and the silicon-based negative electrode sheets of Comparative Examples 1 to 2 were tested, and the performance comparison diagram was obtained as shown in FIG. Figure 3-7 As shown, the capacity, coulombic efficiency and capacity retention rate are summarized in Table 1.
[0100] Table 1
[0101]
[0102] It can be seen from Table 1 that the first-cycle coulomb efficiency of the silicon-based negative electrode plates after adding the single-walled carbon nanotubes with five-membered ring and seven-membered ring defects has been significantly improved, from less than 50% of the control group to more than 78.5%; at the same time, great progress has also been made in long-cycle stability, and the capacity retention rate has been greatly improved, which significantly proves the effect of the defective single-walled carbon nanotubes on improving the performance of silicon-based negative electrode plates.
[0103] In summary, the high-performance silicon-based composite negative electrode sheet prepared by the present invention can utilize the addition of defective carbon nanotubes to improve the performance of negative electrode sheets containing silicon-based active materials in lithium-ion batteries or lithium-ion secondary batteries, and utilize the strong local stress generated by silicon-based materials during the charging and expansion stage to cause high strain on defective carbon nanotubes, thereby enhancing the chemical activity of atoms at the defective sites, thereby generating a "stress-chemical interface coupling effect" between lithium atoms and silicon group clusters under the action of lithium atoms, anchoring silicon group clusters in situ to avoid electrical contact loss, and at the same time, silicon group clusters can also separate defective carbon nanotube bundles to enhance the transmission rate of lithium ions.
[0104] The present invention utilizes "stress-chemical interface coupling" to reconstruct the three-dimensional structure within the silicon-based negative electrode, thereby stabilizing the electrode structure and promoting mass transfer, thereby effectively improving its rate and cycle performance.
[0105] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a high-performance silicon-based composite negative electrode sheet, characterized in that: The following steps are involved: Step 1: dispersing a certain amount of surfactant and a certain amount of defective single-walled carbon nanotubes in a solvent I by ultrasonic treatment, and then centrifuging to obtain a stable and uniform dispersion A; Step 2: Mix the silicon-based active material, the binder, the carbon-based conductive agent and the dispersion A in step 1 in a certain proportion by wet mixing to prepare a mixed slurry; Step 3: coating the mixed slurry prepared in step 2 on a conductive substrate, drying, and cutting to obtain the high-performance silicon-based composite negative electrode plate.
2. The preparation method according to claim 1, characterized in that The surfactant described in step 1 is one or more of carboxymethyl cellulose, polyvinyl pyrrolidone, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, and sodium lignin sulfonate; the solvent I described in step 1 is one or more of water, ethanol, N-methylpyrrolidone, etc.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the defective single-walled carbon nanotubes in step 1 to the surfactant is (0.01-20):1; the mass ratio of the defective single-walled carbon nanotubes in step 1 to the solvent I is (0.001-1):
1.
4. The preparation method according to claim 1, characterized in that: The ultrasonic treatment method in step 1 is to treat at a temperature of -10 to 10°C for 1 to 3 hours; the ultrasonic power is 100 to 2000 watts.
5. The preparation method according to claim 1, characterized in that: In step 2, the mass ratio of the silicon-based active material, the binder, the carbon-based conductive agent and the defective single-walled carbon nanotube is (0.1-96): (0.01-25): (0.01-25): (0.001-5).
6. The preparation method according to claim 1, characterized in that: The silicon-based active material in step 2 is one or more of elemental silicon, silicon monoxide and silicon-carbon composite materials, or a composite of one or more of elemental silicon, silicon monoxide and silicon-carbon composite materials and graphite; The binder in step 2 is one or more of carboxymethyl cellulose, sodium alginate, ammonium alginate, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylic acid, lithiated polyacrylic acid, styrene-butadiene rubber and polystyrene-butadiene copolymer; In step 2, the carbon-based conductive agent is one or more of artificial graphite, natural graphite, hard carbon, soft carbon, acetylene black, Ketjen black, carbon black SuperP, graphene, multi-walled carbon nanotubes and fibrous carbon.
7. The preparation method according to claim 1, characterized in that: The conductive substrate in step 3 is any one of copper foil, carbon-coated copper foil, copper mesh, foam copper, stainless steel, stainless steel mesh, carbon paper and carbon cloth.
8. A high-performance silicon-based composite negative electrode sheet prepared by the method according to any one of claims 1 to 7.
9. Use of the high-performance silicon-based composite negative electrode sheet according to claim 8 in the preparation of lithium-ion batteries or lithium-ion secondary batteries.
10. A method for preparing a lithium ion battery or a lithium ion secondary battery using the high performance silicon-based composite negative electrode sheet according to claim 8, comprising the following steps: a) Preparation of electrode sheet: making the high-performance silicon-based composite negative electrode sheet into a button-type electrode disc; b) Button cell assembly: Using the metal lithium sheet as the counter electrode, the electrode disc prepared in step a), the metal lithium sheet, the separator, and the electrolyte are assembled into a button cell. The battery model is a CR2032 button cell.
Citation Information
Patent Citations
Preparation method of silicon-based negative electrode material
CN115132982A
Silicon-carbon nanotube composite material, preparation method and application
CN116314698A
Low-defect carbon nanotube sludge and preparation method therefor, conductive composite material based on the low-defect carbon nanotube, negative electrode slurry using same, negative electrode, and lithium secondary battery
WO2023068531A1
Aqueous carbon nanotube dispersion, paste, cathode and anode
WO2023128801A1
Cited By
Foamy copper-based lithium ion battery negative electrode material as well as preparation method and application thereof
CN120809783A
Preparation method of high-safety soft package lithium battery
CN121416633A
